Sulfasalazine augments a pro‐inflammatory response in interleukin‐1β‐stimulated amniocytes and myocytes. Issue 4 (3rd November 2015) - Sykes, Lynne; Thomson, Kacie R.; Boyce, Emily J.; Lee, Yun S.; Rasheed, Zahirrah B. M.; MacIntyre, David A.; Teoh, Tiong Ghee; Bennett, Phillip R.
Summary: Preterm birth occurs in 10% of pregnancies and is a major cause of neonatal morbidity and mortality. The majority of cases of early preterm labour are associated with infection/inflammation, which places the fetal central nervous system at risk. Targeting immune activation is therefore an appealing therapeutic strategy for the prevention of preterm labour and neonatal brain injury. The expression of many labour‐associated and inflammatory‐response genes is controlled by the transcription factors nuclear factor‐ κ B (NF‐ κ B) and activator protein‐1 (AP‐1), which makes them therapeutic targets of interest. Sulfasalazine (SASP) has been shown to inhibit NF‐ κ B and reduce lipopolysaccharide‐induced cytokine concentrations in fetal membrane explants and reduce the rate of Escherichia coli ‐induced preterm labour in mice. Its effects upon AP‐1 in the context of pregnancy are unknown. In this study the effect of SASP on interleukin‐1 β (IL‐1 β ) ‐induced NF‐ κ B and AP‐1 activity, cytokine production and cyclo‐oxygenase‐2 (COX‐2) expression was examined in amniocytes and myocytes. A supra‐therapeutic concentration (5 mm ) was required to inhibit IL‐1 β ‐induced NF‐ κ B ( P < 0·0001) in amniocytes and IL‐1 β ‐induced NF‐ κ B ( P < 0·01), AP‐1 ( P < 0·01) and COX‐2 ( P < 0·05) in myocytes. Despite inhibiting IL‐1 β ‐induced cytokines, a basal increase in IL‐6 ( P < 0·01), IL‐8 ( P < 0·0001) and tumour necrosis factor‐ α (TNF‐ α ) ( P < 0·001) was seen with 5 mm SASP in amniocytes, and significant cytotoxic effects were seen in myocytes. The therapeutic concentration of 0·015 mm had no inhibitory effects on pro‐inflammatory mediators, but led to an augmented response to IL‐1 β ‐induced IL‐6 ( P < 0·01), IL‐8 ( P < 0·05) and TNF‐ α ( P < 0·05) in amniocytes and IL‐8 ( P < 0·05) in myocytes. SASP is therefore an unlikely therapeutic candidate for the prevention of inflammation‐induced preterm labour.